The Role of Epigenetics in Autoimmune/Inflammatory Disease - Surace, Anna Elisa Andrea; Hedrich, Christian M. (Frontiers in Immunology, 2019)
Historically, systemic self-inflammatory conditions were classified as either autoinflammatory and caused by the innate immune system or autoimmune and driven by adaptive immune responses. However, it became clear that reality is much more complex and that autoimmune/inflammatory conditions range along an “inflammatory spectrum” with primarily autoinflammatory vs. autoimmune conditions resembling extremes at either end. Epigenetic modifications influence gene expression and alter cellular functions without modifying the genomic sequence. Methylation of CpG DNA dinucleotides and/or their hydroxymethylation, post-translational modifications to amino termini of histone proteins, and non-coding RNA expression are main epigenetic events. The pathophysiology of autoimmune/inflammatory diseases has been closely linked with disease causing gene mutations (rare) or a combination of genetic susceptibility and epigenetic modifications arising from exposure to the environment (more common). Over recent years, progress has been made in understanding molecular mechanisms involved in systemic inflammation and the contribution of innate and adaptive immune responses. Epigenetic events have been identified as i) central pathophysiological factors in addition to genetic disease predisposition and ii) as co-factors determining clinical pictures and outcomes in individuals with mono-genic disease. Thus, a complete understanding of epigenetic contributors to autoimmune/inflammatory disease will result in approaches to predict individual disease outcomes and the introduction of effective, target-directed and tolerable therapies. Here, we summarize recent findings that signify the importance of epigenetic modifications in autoimmune/inflammatory disorders along the inflammatory spectrum choosing three examples: the autoinflammatory bone condition chronic nonbacterial osteomyelitis (CNO), the “mixed pattern” disorder psoriasis, and the autoimmune disease systemic lupus erythematosus (SLE).